3D Interactive Multimedia with a Contextual Approach in English Subjects - Wahyuningsih, Linda; Parmiti, Desak Putu (International Journal of Elementary Education, 2023)
Various technological improvements were developed to be able to help achieve each material competency in learning. This study aims to: (1) find out the design and development of interactive multimedia with a contextual approach, (2) find out the validity of interactive multimedia with a contextual approach (3) find out the effectiveness of interactive multimedia with a contextual approach in English. This type of research is development using the ADDIE model. Data collection was carried out by recording documents, interviews, questionnaires and tests. The data analysis used is descriptive qualitative analysis, quantitative and inferential statistics. The results of this study are (1) Interactive multimedia is developed using the ADDIE model through 5 stages (analyze, design, development, implementation, evaluation); (2) the validity of interactive multimedia based on the results of the review by content experts and media experts was 96%, the results of the design expert's review were 94.66%, the results of individual trials were 95.88% and small group trials were 98.2% ( 3) the effectiveness of interactive multimedia shows an average pre-test of 52.2 and a post-test score of 81.9. After calculating using the t-test, the results obtained are t-count of 12,595 > t-table 2,074. So H0 is rejected and H1 is accepted. Thus, interactive multimedia with a contextual approach which was developed is effective for improving students' learning outcomes in English.